PENGARUH LITERASI KEUANGAN, KONTROL DIRI DAN TEMAN SEBAYA TERHADAP SAVING BEHAVIOR PADA ANAK SEKOLAH MENENGAH ATAS NEGRI 10 TASIKMALAYA - Violita Renata Nurseptia; Astri Srigustini; Edi Fitriana Afriza (JOURNAL SAINS STUDENT RESEARCH, 2024)
The problem in research is that saving behavior in school children is still low. The aim of this research is to determine "The Influence of Financial Literacy, Self-Control and Peers on Saving Behavior in Tasikmalaya State 10 Senior High School Children". This research uses quantitative research with survey methods. The population in this study were students in class X and XI of SMA N 10 Tasikmalaya. The technique for taking this sample is using simple random sampling, totaling 281 samples. The data collection technique in this research is using questionnaires and data analysis techniques using SPSS version 25. The results of this research show that financial literacy has a positive and significant effect on saving behavior, self-control has a positive and significant effect on saving behavior, peers have a positive effect and significant to saving behavior. Simultaneously, it shows that financial literacy, self-control and peers have a positive and significant effect on saving behavior.